Ceracis luci sp. nov., the first Ciidae species (Coleoptera: Tenebrionoidea) from the Caatinga biome - Souza-Gonçalves, Igor; Lopes-Andrade, Cristiano (Zootaxa, 2024)
Ceracis luci sp. nov., the first Ciidae species from the Caatinga biome, is described based on individuals collected in Licínio de Almeida, in the state of Bahia, Northeast Brazil. The species is recognizable mainly by the following characteristics: antennae with 8 antennomeres and subseriate elytral punctation; male anterocephalic edge produced forward and slightly elevated upward forming a wide lamina with a straight edge (when seen from above); male anterior edge of pronotum produced forward as a plate deeply emarginate at middle forming two horns, almost parallel to each other and with rounded apices; and female ovipositor lacking gonostyli. Ceracis luci sp. nov. is morphologically similar to Ceracis pullulus (Casey), for which we provide information on the morphology of the abdominal terminalia of males and females and new geographic distribution records.